The Queen’s Favorite Unknown Dramatist: Were There Other Royal Plays By Shakespeare? A Research Inquiry - Chiljan, Katherine (Journal of Scientific Exploration, 2023)
Surviving records of Queen Elizabeth’s revels briefly list performance dates, expenses, and sometimes titles of plays and masques that she had seen. Evidence suggests that, sometimes under titles different from the ones we know, the queen viewed at least 18 different Shakespeare plays – about half the canon – clearly proving him as her favorite dramatist. The most obvious example is royal performances of The History of Error in 1577 and 1583, and Shakespeare’s The Comedy of Errors. King James, Elizabeth’s successor, saw at least 17 Shakespeare plays. Yet no evidence exists that either monarch knew, met or corresponded with anyone named William Shakespeare. And no one in the court of either Elizabeth or James ever claimed to have known William Shakspere of Stratford-upon-Avon during his lifetime or had anything to say when he died. This blankness supports the notion that the name was a pseudonym for someone wishing to remain publicly anonymous. This essay – and its attached research inquiry – examines the plays and masques performed at Elizabeth’s court and suggests that many of them were actually Shakespeare plays. If so, then they precede traditional Shakespeare play composition dates by a decade or more, which, in many cases, would invalidate the Stratford man’s authorship, and favor the idea that the true author was writing anonymously.